2014
DOI: 10.1103/physrevlett.113.030601
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of the Role of Mutual Information in the Nonequilibrium Dynamics of a Maxwell Demon

Abstract: We validate experimentally a fluctuation relation known as generalized Jarzynski equality governing the work distribution in a feedback-controlled system. The feedback control is performed on a single electron box analogously to the original Szilard engine. In the generalized Jarzynski equality, mutual information is treated on an equal footing with the thermodynamic work. Our measurements provide the first evidence of the role of mutual information in the fluctuation theorem and thermodynamics of irreversible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
261
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(263 citation statements)
references
References 35 publications
2
261
0
Order By: Relevance
“…[32]. But experimentally, Maxwell's demon was realized in such a circuit only very recently [33,34]. Here we briefly discuss the principle of the demon, and the results of the experiments performed on an SEB (see Fig.…”
Section: The Role Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…[32]. But experimentally, Maxwell's demon was realized in such a circuit only very recently [33,34]. Here we briefly discuss the principle of the demon, and the results of the experiments performed on an SEB (see Fig.…”
Section: The Role Of Informationmentioning
confidence: 99%
“…In ref. [34], the influence of measurement errors of the demon were considered using the concept of mutual information I. The measurement on an SEB demonstrated that under the feedback conditions the histograms of the type shown in Fig.…”
Section: The Role Of Informationmentioning
confidence: 99%
“…Using superconducting circuits, we reveal the inner mechanics of a quantum Maxwell demon that is able to extract work from a quantum system. Importantly, we are able to directly probe the extracted work by measuring the output power emitted by the system through stimulated emission, without inferring it from system trajectories (3)(4)(5)(6)14). We are thus able to demonstrate how the information stored in the demon's memory affects the extracted work.…”
mentioning
confidence: 99%
“…This paradox was resolved a century later when Landauer realized that information processing has an entropic cost and Bennett argued that the demon's memory must take full part in the thermodynamic cycle (2). Recent experiments have realized classical versions of elementary Maxwell demons in various physical systems (3)(4)(5)(6)(7)(8). Although quantum versions have long been investigated theoretically (9)(10)(11)(12)(13), experimental realizations are in their infancy (7,8), and a full characterization is still missing.…”
mentioning
confidence: 99%
“…We would emphasize that the informational entropy (i.e., the von Neumann entropy) of such a genuine quantum system never increases, but is always zero [37]. In this sense, a fundamental gap between the microscopic and macroscopic worlds has not yet been bridged: How does the second law emerge from pure quantum states?In a rather different context, a general theory of the second law and its connection to information has recently been developed even out of equilibrium [38][39][40][41], which has also been experimentally verified in laboratories [42][43][44][45]. This has revealed that information contents and thermodynamic quantities can be treated on an equal footing, as originally illustrated by Szilard and Landauer in the context of Maxwell's demon [46,47].…”
mentioning
confidence: 99%